Relationships between self perceptions and physical activity behaviour, fear of falling, and physical function among older adults - Sales, Myrla (Eur Rev Aging Phys Act, 2017)
BACKGROUND: There has been a lack of research examining the relationship among self-perceptions, behaviour, cognitions and functioning in older adults. This study, therefore, examined the relationship between global and physical self-perceptions, physical activity behaviour, and fear of falling taking into considerations objective measures of physical functioning in community dwelling older adults. METHODS/DESIGN: Sixty-six participants between 60 and 90 years old (71.9 ± 6.6 years; 47 females; 19 males) completed questionnaires assessing physical and global self-description (PSDQ), planned and incidental physical activity behaviour (IPEQ), and falls efficacy (Short FES-I) as well as tests measuring physical functioning. Backwards multiple linear regression modelling was used to assess possible relationships among variables. RESULTS: Findings showed that physical self-perceptions (activity, coordination, endurance, flexibility) were associated with self-reported planned and incidental PA whereas sit-to-stand was the only objectively measured physical functioning variable associated with planned PA. Similarly, more falls, global self-esteem, general physical and domain specific physical self-perceptions (flexibility and strength) as well as knee strength were associated with fear of falling. There were also associations between some of the objectively measured physical functioning variables and self-perceptions of the physical self, providing some predictive validity for the PDSQ. CONCLUSIONS: The findings of this study come to corroborate that the belief system of older adults ideally need to be taken into consideration when designing interventions that aim to enhance PA behaviour or reduce fear of falling. Coupling that with goal-setting, life coaching and behaviour change strategies would also be beneficial to address engagement and adherence to such interventions. TRIAL REGISTRATION: This trial was retrospectively registered with the Australian New Zealand Clinical Trials Registry - Registry No. ACTRN12614000700639 on the Jul 03rd 2014.